Upaya Untuk Melindungi Diri Dari Risiko Kesehatan Bagi Kelompok Pemulung Di Tempat Pembuangan Akhir Sampah Di Kota Makassar - Hilal, Achmad; Herman, Herman; W, Rizky Rahadian; Asrianto, Asrianto; Jabir, M. Agus; Betan, Abu Bakar (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2024)
A scavenger is a person who collects and processes waste on roads, rivers, rubbish bins and final disposal sites as a market commodity. Scavengers are a social group whose work is to collect or sort items that are considered useful from rubbish, both in TPAs ​​(Final Disposal Sites) and outside TPAs. The aim of this PkM is to improve the level of health and standard of living as well as to protect themselves from the health risks that the scavenger group faces. The methods provided are health counseling and education in an effort to prevent various infectious diseases and work-related accidents which can be caused by direct contact with continuous waste and also the minimal use of personal protective equipment when scavenging. The expected results of community service activities are preventing and minimizing the occurrence of infectious diseases that may arise as well as ensuring safety and security while they work, increasing income and skills in processing waste into useful and marketable materials.